Hepatitis C virus serine protease: synthesis of radioactive and stable isotope‐labeled potent inhibitors. (13th February 2014) - Latli, Bachir; Hrapchak, Matt; Gorys, Vida; Llinàs‐Brunet, Montse; Campbell, Scot S.; Song, Jinhua; Senanayake, Chris H.
<x xml:space="preserve">Abstract</x> Drug candidates labeled with radioactive and stable isotopes are required for absorption, distribution, metabolism, and excretion (ADME) studies, pharmacokinetics, autoradiography, bioanalytical, and other research activities. The findings from these studies are crucial in the development of a drug candidate and its approval for human use. Herein, we report the synthesis of potent and selective hepatitis C virus serine protease inhibitors related to BILN 2061 and BI 201335 labeled with radioactive and stable isotopes. Synthetic efforts were focused on the common substituted thiazole moiety, which is easily accessible via a Hantzsch's reaction of α‐bromoketones and mono‐substituted thioureas. In the radioactive synthesis, commercially available carbon‐14 thiourea was utilized to prepare mono‐substituted thioureas, which upon condensation with α‐bromoketones in isopropanol followed by ester hydrolysis gave the desired carbon‐14‐labeled protease inhibitors. The same strategy was used to prepare these inhibitors labeled with stable isotopes. Mono‐substituted thioureas were obtained from commercially available deuterium‐labeled intermediates and then condensed with α‐bromoketones followed by ester hydrolysis to give the deuterium‐labeled inhibitors.